Chiang Kai-shek's politics of shame : leadership, legacy, and national identity in China - Huang, Grace C. (Harvard East Asian monographs, 2021)
"Reconsiders Chiang's leadership and legacy by drawing on an extraordinary and uncensored collection of his diaries, telegrams, and speeches stitched together by his secretaries. Huang paints a new intriguing portrait of this 20th century leader who advanced a Confucian politics of shame to confront Japanese incursion into China and urge unity among his people. In also comparing Chiang's response to imperialism to those of Mao, Yuan Shikai, and Mahatma Gandhi, Huang widens the implications of her findings to explore alternatives to Western expressions of nationalism and modernity"--